Structural violence and the 1962-1963 tuberculosis epidemic in Eskimo Point, N.W.T. - Tester, Frank; McNicoll, Paule; Tran, Quyen (Études/Inuit/Studies, 2012)
In the winter of 1962-1963, an epidemic of tuberculosis broke out in Eskimo Point, an Inuit community on the west coast of Hudson Bay in the Canadian Arctic. The outbreak was made possible by bad living conditions, among the worst ever documented in the history of the Canadian Arctic. The epidemic reveals the intersection of social attitudes, the economic logic of a postwar Canadian welfare state, and the difficult transition being made by Inuit moving from tents, igloos, and land-based camps to settlements along the Arctic coast. It is a case of “structural violence” where rules, policies, and social institutions operate in ways that cause physical and psychological harm to people lacking the power and/or resources necessary to changing the social systems and conditions in which they live. Both individuals and entire communities are affected. With regard to past—and present—Inuit housing conditions, we invoke the concept of structural violence to stress the importance of identifying and speaking about public health problems as a violation of internationally recognised human rights.